Romantic Outlaws, Beloved Prisons The Unconscious Meanings of Crime and Punishment - Duncan, Martha Grace (NYU Press, 1996)
An ex-convict struggles with his addictive yearning for prison. A law-abiding citizen broods over his pleasure in violent, illegal acts. A prison warden loses his job because he is so successful in rehabilitating criminals. These are but a few of the intriguing stories Martha Grace Duncan examines in her bold, interdisciplinary book Romantic Outlaws, Beloved Prisons. Duncan writes: "This is a book about paradoxes and mingled yarns - about the bright sides of dark events, the silver linings of sable clouds." She portrays upright citizens who harbor a strange liking for criminal deeds, and criminals who conceive of prison in positive terms: as a nurturing mother, an academy, a matrix of spiritual rebirth, or a refuge from life's trivia. In developing her unique vision, Duncan draws on literature, history, psychoanalysis, and law. Her work reveals a nonutopian world in which criminals and non-criminals--while injuring each other in obvious ways--nonetheless live together in a symbiotic as well as an adversarial relationship, needing each other, serving each other, enriching each other's lives in profound and surprising fashion.